Development of a method for automated integration of the “Pentagon” testing model into a continuous integration and delivery pipeline for microservice software - Kuzmych, Oleh; Seniv, Maksym (Eastern-European Journal of Enterprise Technologies, 2026)
This study investigates the process of verifying the reliability of software with a microservice architecture, developed by several teams in parallel. The task addressed relates to the lack of cost-effective methods for automated integration of testing models into continuous integration and delivery (CI/CD) pipelines adapted to the microservice architecture. This leads to the emergence of "blind spots" in the field of functional and non-functional requirements and excessive time consumption of developers. This paper reports a method devised for automated integration of the Pentagon testing model into a multi-stage continuous integration and delivery pipeline. The method implements the cumulative principle of progressive distribution of six testing layers between four isolated environments: DEV (development), TEST (test), PRE-PROD (pre-production), and PROD (production). The devised method guarantees coverage of all six layers during each change in the code base. The key feature of the method is to eliminate the influence of human factor on decisions to launch tests. This makes it possible to achieve increased reliability values, namely Defect Removal Efficiency (DRE), while the manual method detects on average only 27% of defects. The devised method reduces the time when the developer is involved in the process of running tests by 70% compared to the manual approach. For 100 commits (fixing the current state of authentic code and files in the local repository) per month, the savings compared to the manual method are 37%. The method is suitable for verifying software with a microservice architecture, which is deployed on cloud platforms (Amazon Web Services, USA; Azure, USA; Google Cloud, USA) with support for automated testing and container orchestration